Heterogeneous nuclear ribonucleoprotein C promotes non-small cell lung cancer progression by enhancing XB130 mRNA stability and translation - Qinrong Wang; Xuanjing Gou; Lingling Liu; Daolan Deng; Yan Zhao; Jianjiang Zhou; Yuan Xie; Yinhui Jiang; Jianglun Li; Jian Zhang; Ying Liu (Cancer Cell International)
Abstract Background XB130, a classical adaptor protein, exerts a critical role in diverse cellular processes. Aberrant expression of XB130 is closely associated with tumorigenesis and aggressiveness. However, the mechanisms governing its expression regulation remain poorly understood. Heterogeneous nuclear ribonucleoprotein C (hnRNPC), as an RNA-binding protein, is known to modulate multiple aspects of RNA metabolism and has been implicated in the pathogenesis of various cancers. We have previously discovered that hnRNPC is one of the candidate proteins that interact with the 3’ untranslated region (3’UTR) of XB130 in non-small cell lung cancer (NSCLC). Therefore, this study aims to comprehensively elucidate how hnRNPC regulates the expression of XB130 in NSCLC. Materials and methods We evaluated the expression of hnRNPC in cancer and assessed the correlation between hnRNPC expression and prognosis in cancer patients using public databases. Subsequently, several stable cell lines were constructed. The proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of these cells were detected through Real-time cellular analysis, adherent colony formation, wound healing assay, invasion assay, and Western blotting. The specific regulatory manner between hnRNPC and XB130 was investigated by Real-time quantitative PCR, Western blotting, RNA pull‑down assay, dual‑luciferase reporter assay, RNA immunoprecipitation, and Co-Immunoprecipitation. Results We identified that hnRNPC expression is significantly elevated in NSCLC and correlates with poor prognosis in patients with lung adenocarcinoma. HnRNPC overexpression in NSCLC cells increased the expression of XB130, subsequently activating the PI3K/Akt signaling pathway and ultimately promoting cell proliferation and EMT. Additionally, overexpressing XB130 in hnRNPC-silenced cells partially restored cell proliferation and EMT. Mechanistically, hnRNPC specifically bound to the 3’UTR segments of XB130 mRNA, enhancing mRNA stability by inhibiting the recruitment of nucleases 5’-3’ exoribonuclease 1 (XRN1) and DIS3-like 3’-5’ exoribonuclease 2 (DIS3L2). Furthermore, hnRNPC simultaneously interacted with the eukaryotic initiation factor 4E (eIF4E), a component of the eIF4F complex, facilitating the circularization of XB130 mRNA and thereby increasing its translation efficiency. Conclusions HnRNPC overexpression promotes NSCLC progression by enhancing XB130 mRNA stability and translation, suggesting that hnRNPC might be a potential therapeutic and prognostic target for NSCLC.